2015
DOI: 10.1103/physrevb.91.045408
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic mechanisms for bilayer growth of graphene on metal substrates

Abstract: Epitaxial growth on metal substrates has been shown to be the most powerful approach in producing large-scale high-quality monolayer graphene, yet it remains a major challenge to realize uniform bilayer graphene growth. Here we carry out a comparative study of the atomistic mechanisms for bilayer graphene growth on the (111) surfaces of Cu and Ni, using multi-scale approaches combining first-principles calculations and rate equation analysis. We first show that the relatively weak graphene-Cu interaction enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 54 publications
(48 reference statements)
3
39
0
Order By: Relevance
“…For graphene/Cu, similar C stacking on H3 and T1 is the most stable, as it is more stable by 0.004 eV than C on T4 and T1. This result is consistent with the previous theoretical report on graphene/Cu(111) [15]. The distance between the graphene sheet and the Cu surface is 3.57 Å.…”
Section: Resultssupporting
confidence: 93%
“…For graphene/Cu, similar C stacking on H3 and T1 is the most stable, as it is more stable by 0.004 eV than C on T4 and T1. This result is consistent with the previous theoretical report on graphene/Cu(111) [15]. The distance between the graphene sheet and the Cu surface is 3.57 Å.…”
Section: Resultssupporting
confidence: 93%
“…More importantly, the central finding of this study, namely, the identification of carbon dimers as the dominant species, also calls for the need to reassess earlier understandings of the atomistic mechanisms of graphene growth both experimentally and theoretically. Taking bilayer graphene growth as a specific example, several recent studies [29][30][31] have reported experimental observations or developed kinetic models primarily based on considerations of carbon monomers as the dominant species. It would be intriguing to see how the identification of carbon dimers as the dominant feeding species will change the kinetic mechanisms.…”
mentioning
confidence: 99%
“…The second graphene layer is found to grow beneath the first layer through the atom‐exchange process and the ensuing C penetration onto the Cu surface . A comparative first‐principles study of graphene bilayer growth on Cu(111) and Ni(111) revealed that Cu(111) is a more proper substrate for bilayer growth, because of the weaker interactions at the graphene–Cu interface than those at the graphene–Ni interface: The weaker interactions enhance the lateral diffusion and lead to effective C nucleation underneath the first layer (Figure ). It was also found that there is a critical graphene size beyond which nucleation of the second layer is initiated .…”
Section: Growth Of Graphenementioning
confidence: 99%
“…A comparative first‐principles study of graphene bilayer growth on Cu(111) and Ni(111) revealed that Cu(111) is a more proper substrate for bilayer growth, because of the weaker interactions at the graphene–Cu interface than those at the graphene–Ni interface: The weaker interactions enhance the lateral diffusion and lead to effective C nucleation underneath the first layer (Figure ). It was also found that there is a critical graphene size beyond which nucleation of the second layer is initiated . It should also be cautioned that, the bilayer growth picture developed based on C monomer attachment at the island edges may need to be further developed by considering the relatively easier attachment of C–C dimers revealed recently .…”
Section: Growth Of Graphenementioning
confidence: 99%
See 1 more Smart Citation